Current and Future Pharmacopoeial Requirements for the Quality of Extemporaneous Medicinal Products: A Review of Regulatory Standards - L. I. Shishova; A. V. Yarutkin; V. L. Bagirova (Регуляторные исследования и экспертиза лекарственных средств)
INTRODUCTION. The organisation of extemporaneous compounding in pharmacies is currently considered to be a priority for the national healthcare system. Extemporaneous medicinal products used by patients should meet high quality, safety, and efficacy standards. Provision of consistent and science-based requirements for the quality of medicines, particularly those compounded in pharmacies, is a key area of concern for standardisation.AIM. This study aimed to analyse international experience and determine areas for the improvement of standardisation approaches of the State Pharmacopoeia of the Russian Federation to the quality of medicinal products compounded in pharmacies.DISCUSSION. The study investigated the common and distinctive properties of extemporaneous preparations compounded in pharmacies (and not subject to registration) and medicinal products manufactured by pharmaceutical companies. The authors analysed the requirements and recommendations for compounding and quality assurance of extemporaneous medicinal products provided by the regulatory and pharmacopoeial authorities of the Russian Federation, the Republic of Belarus, the European Union, the United Kingdom, the USA, and Canada. The United States Pharmacopeia includes circa 150 individual monographs for non-sterile compounded drug products with particular compositions and over 20 individual monographs for sterile compounded drug products. The European Pharmacopoeia requires that extemporaneous preparation should be organised within the quality assurance framework of a pharmacy after a proper risk assessment. In the Republic of Belarus, extemporaneous medicinal products are compounded in line with the requirements of the Good Compounding Practices and the State Pharmacopoeia of the Republic of Belarus, which provide rapid testing procedures for extemporaneous medicinal products.CONCLUSIONS. The study identified the following areas for the development of requirements for the quality of medicinal products compounded in pharmacies: the determination of rapid testing approaches; the development of pharmacopoeial monographs for active pharmaceutical substances used in extemporaneous compounding, with the Identification section supplemented with an additional subsection on pharmacy-specific analytical procedures; and the development of pharmacopoeial monographs for frequently used compounding formulae.